Full-scale experimental study on dynamic behaviors of a three-cable network with a pretensioned cross-tie. (15th April 2023) - Chen, Lin; Qin, Lei; Di, Fangdian; Sun, Limin; Zou, Yiqing; Huang, Zhiquan
Abstract: A cable network of cables interconnected with cross-ties and attached with dampers represents the generalized solution for vibration mitigation of stay cables. It is of significant interest as completely suppressing vibrations of long cables vulnerable to various excitation mechanisms is still challenging. Although many theoretical studies on cable networks exist, large-scale and full-scale experimental validations and investigations are lacking. Therefore, this study first presents a full-scale experiment setup for experimental studies on cable networks, which consists of at most three cables with adjustable length and the maximum length is 41.35 m. The experimental setup is subsequently used for studying effects of a pretensioned cross-tie on cable network dynamics, with the focus placed on the pretension, location and anchoring form of the cross-tie. The experimental results are then discussed in detail with reference to a theoretical model of a three-cable network with cable sag and cross-tie pretension accounted. It is found that the experimental results on system frequencies and mode shapes are consistent with those predicted using the analytical model. Particularly, both the pretensioned cross-tie induced increase and decrease in cable network frequencies have been validated by the experiments. Furthermore, the grounded cross-tie is found to significantly improve the system fundamental frequency, but the increase in frequencies of other local vibration modes is limited. Besides, the test results have validated that a rigid cross-tie has very limited damping effect on the cable network. Highlights: A full-scale experiment setup for experimental studies on cable networks. The effects of the pretensioned cross-tie on cable network dynamics studied experimentally. A theoretical model established for a three-cable network with a pretensioned cross-tie. Experimental validation of the theoretical model and analytical findings.